Tocotrienols inhibit lipopolysaccharide-induced pro-inflammatory cytokines in macrophages of female mice - Morrison David C; Papasian Christopher J; Reis Julia C; Qureshi Asaf A; Qureshi Nilofer (Lipids in Health and Disease, 2010)
Abstract Background Inflammation has been implicated in cardiovascular disease, and the important role of proteasomes in the development of inflammation and other macrophage functions has been demonstrated. Tocotrienols are potent hypocholesterolemic agents that inhibit β-hydroxy-β-methylglutaryl coenzyme A reductase activity, which is degraded via the ubiquitin-proteasome pathway. Our objective was to evaluate the effect of tocotrienols in reducing inflammation. Lipopolysaccharide (LPS) was used as a prototype for inflammation in murine RAW 264.7 cells and BALB/c female mice. Results The present results clearly demonstrate that α-, γ-, or δ-tocotrienol treatments inhibit the chymotrypsin-like activity of 20 S rabbit muscle proteasomes (> 50%; P < 0.05). Chymotrypsin, trypsin, and post-glutamase activities were decreased > 40% (P < 0.05) with low concentrations (< 80 μM), and then increased gradually with concentrations of (80 - 640 μM) in RAW 264.7 whole cells. Tocotrienols showed 9 - 33% (P < 0.05) inhibitions in TNF-α secretion in LPS-stimulated RAW 264.7 cells. Results of experiments carried out in BALB/c mice demonstrated that serum levels of TNF-α after LPS treatment were also reduced (20 - 48%; P < 0.05) by tocotrienols with doses of 1 and 10 μg/kg, and a corresponding rise in serum levels of corticosterone (19 - 41%; P < 0.05) and adrenocorticotropic hormone (81 - 145%; P < 0.02) was observed at higher concentrations (40 μM). Maximal inhibition of LPS-induced TNF-α was obtained with δ-tocotrienol (10 μg/kg). Low concentrations of δ-Tocotrienols (< 20 μM) blocked LPS-induced gene expression of TNF-α, IL-1β, IL-6 and iNOS (> 40%), while higher concentrations (40 μM) increased gene expression of the latter in peritoneal macrophages (prepared from BALB/c mice) as compared to control group. Conclusions These results represent a novel approach by using natural products, such as tocotrienols as proteasome modulators, which may lead to the development of new dietary supplements of tocotrienols for cardiovascular diseases, as well as others that are based on inflammation.